Balancing Priorities: Decision-Making in Sustainable Supply Chain Management - Wu,Zhaohui; Pagell,Mark (Journal of Operations Management, 2011)
Keywords: Management; Supply Chain

Building a More Complete Theory of Sustainable Supply Chain Management Using Case Studies of Ten Exemplars - Pagell,Mark; Wu,Zhaohui (Journal of Supply Chain Management, 2009)
Case studies of 10 exemplar firms are used to build a coherent and testable model of the elements necessary to create a sustainable supply chain. The cases build on previous research by examining the chain as an entirety, by explicitly examining both the social and environmental outcomes of the chain's activities, and by explicitly asking what these exemplar organizations are doing that is unique in regards to managing their supply chains in a sustainable manner. The analysis suggests that the practices that lead to a more sustainable supply chain are equal parts best practices in traditional supply chain management and new behaviors, some of which run counter to existing accepted “best” practice.
Keywords: Management; Supply Chain

Business Education and Its Relationship to Student Personal Moral Philosophies and Attitudes Toward Profits: An Empirical Response to Critics - Neubaum,Donald; Pagell,Mark; Drexler,John; Ryan,Fran McKee; Larson,Erik (Academy of Management Learning and Education, 2009)
Critics of business education (e.g., Ghoshal, 2005; Mitroff, 2004) place much of the blame for recent ethical scandals on the lack of moral development of managers and the amoral, "profits-first" theoretical underpinnings of business education. To empirically test these claims, we surveyed 1,080 business and nonbusiness students from a major research university. The results suggest that neither the personal moral philosophies of business and nonbusiness students, nor the personal moral philosophies of business freshmen and business seniors differed significantly. Based on our results, we found no evidence to support the claims of critics who suggest business education is associated with negative personal moral philosophies of students. Further, the attitudes of business freshmen and business seniors concerning profit and sustainability differed significantly, yet in the direction opposite the one Ghoshal (2005) and others would have predicted. Thus, blaming the rash of ethical scandals on the amoral and "profits-first" theoretical underpinnings of business school training might be too simplistic of an approach.
Keywords: Management; Strategy & Entrepreneurship

Business education, personal moral philosophies and “profits-first” mentalities: An empirical response to critics - Neubaum,Donald; Drexler,John; Larson,Erik; Pagell,Mark; McKee-Ryan,Fran (Academy of Management Annual Meeting, 2006)
Keywords: Management; Strategy & Entrepreneurship

Building Prevention Capabilities: A Resource-Based Approach to Environmental Performance Advantages - Pagell,Mark; Walton,S.; Wasserman,M.; Handfield,R. (Decision Sciences Institute Conference, 2004)
Keywords: Management

Buyer Behaviors and Supply Chain Performance: An International Exploration - Pagell,Mark; Sheu,C. (Academy of Management Meeting, 2001)
Keywords: Management